Intrinsic biochemical and functional differences in bronchial epithelial cells of children with asthma - Kicic, Anthony; Sutanto, E.N.; Stevens, P.T.; Knight, D.A.; Stick, S.M. (AMER THORACIC SOC, 2006)
Rationale: Convincing evidence of epithelial damage and aberrant repair exists in adult asthmatic airways, even in the absence of inflammation. However, comparable studies in children have been limited by access and availability of clinical samples. Objectives: To determine whether bronchial epithelial cells from children with asthma are inherently distinct from those obtained from children without asthma. Methods: Epithelial cells were obtained by nonbronchoscopic bronchial brushing of children with mild asthma (n = 7), atopic children without asthma (n = 9), and healthy children (n = 12). Cells were subject to morphologic, biochemical, molecular, and functional assessment. Responses were also compared with commercially available epithelial cultures and the transformed cell line 16HBE140. Results: All epithelial cells exhibited a "cobblestone" morphology, which was maintained throughout culture and repeated passage. Expression of cytokeratin 19 varied, with disease phenotype being greatest in healthy nonatopics and lowest in asthmatics. In contrast, expression of cytokeratin 5/14 was greatest in asthmatic samples and least in healthy nonatopic samples. Asthmatic epithelial cells also spontaneously produced significantly greater amounts of interleukin (IL)-6, prostaglandin E2, and epidermal growth factor, and equivalent amounts of IL-1β and soluble intracellular adhesion molecule-1, but significantly lower amounts of transforming growth factor β1. This profile was maintained through successive passages. Asthmatic epithelial cells also exhibited greater rates of proliferation than nonasthmatic cells. Conclusions: This study has shown that epithelial cells from children with mild asthma are intrinsically different both biochemically and functionally compared with epithelial cells from children without asthma. Importantly, these differences are maintained over successive passages, suggesting that they are not dependent on an in vivo environment.